2020
DOI: 10.3847/1538-3881/ab659b
|View full text |Cite
|
Sign up to set email alerts
|

Pre-discovery Activity of New Interstellar Comet 2I/Borisov beyond 5 au

Abstract: Comet 2I/Borisov, the first unambiguous interstellar comet ever found, was discovered in August 2019 at ∼ 3 au from the Sun on its inbound leg. No pre-discovery detection beyond 3 au has yet been reported, mostly due to the comet's proximity to the Sun as seen from the Earth. Here we present a search for pre-discovery detections of comet Borisov using images taken by the Catalina Sky Survey (CSS), Pan-STARRS and Zwicky Transient Facility (ZTF), with a further comprehensive follow-up campaign being presented in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 54 publications
1
32
1
Order By: Relevance
“…the observed magnitude of r=20.5-21.0. As shown by Ye et al (2020) and confirmed by our work, the actual observed prediscovery r magnitudes are much closer to the brightness model predicted for a comet that has its activity dominated by CO than H 2 O (Fitzsimmons et al 2019). This is supported by the fact that H O is very weakly sublimating at temperatures 150 K at a heliocentric distance >3.5 au, while CO can become volatile much further from the Sun at heliocentric distances exceding 10-100 au (Meech & Svoren 2004).…”
Section: Long-term Light Curve and Volatile-driven Activitymentioning
confidence: 84%
See 4 more Smart Citations
“…the observed magnitude of r=20.5-21.0. As shown by Ye et al (2020) and confirmed by our work, the actual observed prediscovery r magnitudes are much closer to the brightness model predicted for a comet that has its activity dominated by CO than H 2 O (Fitzsimmons et al 2019). This is supported by the fact that H O is very weakly sublimating at temperatures 150 K at a heliocentric distance >3.5 au, while CO can become volatile much further from the Sun at heliocentric distances exceding 10-100 au (Meech & Svoren 2004).…”
Section: Long-term Light Curve and Volatile-driven Activitymentioning
confidence: 84%
“…However, the prediscovery photometry may also be compatible with CO 2 -driven activity where CO 2 can become active at >13 au (Womack et al 2017;Ye et al 2020). As discussed in Section 3.4, a significant production rate of H 2 O is inferred from the observed production of CN and C 2 gas (Fitzsimmons et al 2019;Kareta et al 2020) and is ∼100 kg s −1 comparable, though larger than the H 2 O∼20 kg s −1 production inferred from the detection of the [O I] 6300 Å line taken at further heliocentric distances (McKay et al 2020).…”
Section: Long-term Light Curve and Volatile-driven Activitymentioning
confidence: 91%
See 3 more Smart Citations